Group portrait of the attendees of the 1960 Toyon I meeting - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Toyon I meeting, held August 13-18, 1960 at Monte Toyon in Aptos, California.